Enhancing Student Vocabulary through the Use of the PowToon Application - Sudwintari Sudwintari; Tengku Silvana Sinar; Alemina Perangin Angin; Eddy Setia; Rahmadsyah Rangkuti (VELES Voices of English Language Education Society, 2023)
Vocabulary mastery is crucial for effective language acquisition, enabling learners to comprehend spoken and written words and articulate their thoughts. The PowToon application, with its engaging animated videos, offers an immersive and clear learning experience. This is particularly beneficial for English learners, where proficiency in listening, speaking, reading, and writing is vital. This study investigates the impact of the PowToon application on enhancing students' vocabulary. Utilizing a quantitative approach with a Quasi-Experimental Design, data were gathered through observations and tests. The analysis was based on descriptive statistics. The sample comprised 52 tenth-grade students at Tunas Pelita High School. The experimental group, which used PowToon, had a pretest average of 36.19 compared to the control group's 38.40. However, post-tests revealed a score of 82.31 for the experimental group and 71.70 for the control group, indicating a more significant vocabulary improvement in the PowToon cohort. The findings confirm that the PowToon application positively affects vocabulary acquisition. The research underscores PowToon’s potential to enhance students' comprehension, spelling, and pronunciation of English vocabulary, ultimately bolstering their overall learning outcomes.